(untitled) (The Peerian Journal, 2025)
This study presents a comparative analysis of the epic heroes of three nations: Alpomish from Uzbekistan, Jumong from Korea, and Ilya Muromets from Russia. The research explores their common historical and mythological roots, highlighting how these heroic figures embody the moral and national ideals of their respective cultures. Each character symbolizes courage, justice, patriotism, and perseverance through trials — serving as carriers of cultural memory and identity. By examining these epics, the study reveals shared narrative patterns and mythic archetypes that transcend national boundaries. The findings contribute to a deeper understanding of the universal values embedded in epic literature and the cultural connections between different peoples. Such comparative analyses reveal the transnational nature of folklore and highlight universal human values. Through the figures of epic heroes, both cultural and spiritual similarities and differences among nations can be identified. This fosters intercultural dialogue and promotes a deeper understanding of the shared historical and moral roots of different peoples. At the same time, this approach helps preserve the uniqueness of national folklore and establishes its role within the context of world culture. By emphasizing universal values, folkloric works gain renewed relevance in today’s society, becoming not only national treasures but also valuable sources for all of humanity.